ANALYSIS ON BGP PREFIX HIJACKING IN A SIMULATED ENVIRONMENT - Mohd. Hozair Muhammad Rizal, 1979-, author; Saiful Adli Ismail, supervisor; Sekolah Informatiks Termaju (Kuala Lumpur : Universiti Teknologi Malaysia, 2015)
Thesis (Sarjana Sains (Jaminan Maklumat))-Universiti Teknologi Malaysia, 2015